Experiments on the application of the infrasound method of remote monitoring of snow avalanches in the Khibiny Mountains - A. V. Fedorov; I. S. Fedorov; V. E. Asming; A. Yu. Motorin (Лëд и снег, 2025)
Visual slope observations are still the main method of avalanche detection. As a result, avalanche statistics, especially in remote mountain areas, remain incomplete. Like earthquake forecasting, the avalanche prognosis is a complex task that requires a complete set of data on avalanche activity in the region and meteorologicalobservations. To begin this process, it is necessary to create a remote all-weather automated avalanche monitoring system. The Kola Branch of the Geophysical Service of the Russian Academy of Sciences initiateddeveloping a hardware and software package for the avalanche monitoring. The main function of this complex is the registration of seismic and infrasound signals. Over the last five years, a series of experiments have been conducted in the Khibiny Mountains aimed at registration of forced avalanche releases carried out by the avalanche safety service. During the experiments, signals produced by avalanches were recorded using a broadband seismometer and an array of three low-frequency microphones installed at varying distances from an avalanche source. The results obtained demonstrated the high recording capability of the infrasound method, but also revealed problems associated with the use of the seismic method. Technical solutions have been found and prototypes of software for automated detection of target signals have been created. Thus, the experimental complex to monitor avalanche activity in the Khibiny Mountains has been established. The operation of the complex has shown that infrasound signals generated by the movement of snow mass on the mountain slope allow detecting avalanches with a volume of about 5 thousand m3 at a distance of 7 km. The smallest recorded avalanche had a volume of 0.5 thousand m3 and was located in 2.5 km away from the station.